1. The problem statement, all variables and given/known data Okay so the objective here is to express y(t) = cos(t - b) - cos(t) in the form y(t) = Asin(t - c) where A and c are in terms of b. 2. Relevant equations For easy reference, here is a table of identities: http://www.sosmath.com/trig/Trig5/trig5/trig5.html 3. The attempt at a solution Well, using the sum and difference formulas, I got that y(t) = cost(cosb - 1) + sint*sinb equating this to the desired expression gives cost(cosb - 1) + sint*sinb = Asin(t - c) cost(cosb - 1) + sint*sinb = A(sint)(cosc) - A(cost)(sinc) So thus I determined that cosb - 1 = -Asinc (1) sinb = Acosc (2) Squaring both sides and adding gave me, eventually, A^2 = -2cosb + 1 So would A be +/- sqrt(-2cosb + 1) ? Then I did almost the exact same thing for c simply by moving the -1 on the left side of (1) to the right: cosb = -Asinc + 1 (1*) sinb = Acosc (2) Squaring and adding I got A^2 - 2Asinc = 0 A - 2sinc = 0 sinc = A/2 so then would c = arcsin(A/2)? I don't even know if I am doing this right so any assistance would be great! Thank you.